Seminal characteristics of boars housed in a controlled environment located in the warm tropics - Calatayud-Márquez, Derwin (2021)
The aim of this study was to evaluate the seminal characteristics of boars housed in a controlled environment system in tropical dry forest in a commercial pig farm located in the state of Zulia, Venezuela. In total, 6154 seminal evaluations (volume, total sperm, concentration, motility and number of doses per ejaculate) of 95 boars from the Topigs® commercial line were analysed from September 2006 to July 2010. The boars were housed in a controlled environmental system of hygrothermal comfort (Chore.Time. 2529,676; model 8-B1.5). Average values of 253.2 ± 57.0 ml were observed for seminal volume, 3.59 ± 0.2 for progressive individual motility, 322.1x106 ± 98.2 spermatozoa/ml for sperm concentration, 81.2x109 ± 26.1 total spermatozoa per ejaculate and a production of 27.0 ± 8.7 semen doses for ejaculate. Better seminal production was obtained in January and February and lower values in November and December. There is a highly significant effect (p<0.001) of the month on all seminal characteristics except for volume (p>0.05). The controlled environment housing system does not prevent the notable variation of ejaculates within and between the months evaluated.